2016
DOI: 10.1039/c6cc01554a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of highly substituted γ-hydroxybutenolides through the annulation of keto acids with alkynes and subsequent hydroxyl transposition

Abstract: An efficient synthesis of highly functionalized γ-hydroxybutenolides through BF3-catalyzed annulation of keto acids with alkynes is described. Many advantages such as the use of routine reagents, easy operation, and a 100% atom efficiency are demonstrated in the method. The reaction can be readily scaled up to gram quantities, offering good practicality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 25 publications
0
16
0
1
Order By: Relevance
“…(e), Scheme ] under standard conditions also confirmed that 1,4‐migration of the thio group proceeds in a stepwise mechanism. Furthermore, to confirm whether 1,4‐sulfur migration product 3a was generated via 1,2‐sulfur migration product 2a followed by rearrangement, 2a was treated with BF 3 ⋅OEt 2 under optimized reaction conditions [Eq. (f), Scheme ].…”
Section: Resultsmentioning
confidence: 99%
“…(e), Scheme ] under standard conditions also confirmed that 1,4‐migration of the thio group proceeds in a stepwise mechanism. Furthermore, to confirm whether 1,4‐sulfur migration product 3a was generated via 1,2‐sulfur migration product 2a followed by rearrangement, 2a was treated with BF 3 ⋅OEt 2 under optimized reaction conditions [Eq. (f), Scheme ].…”
Section: Resultsmentioning
confidence: 99%
“…To confirm whether 4a was formed via 1cc by an allylic migration of the sulfur substituent, 1cc was treated under the standard conditions (Eq. d) . However, only the starting materials were recovered.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the plethora of biological activities, several synthetic approaches of trisubstituted γ‐hydroxybutenolides were established either via an Indium mediated Barbier‐type reaction with subsequent lactonization/aerobic oxidation, intramolecular oxo ‐Pauson Khand reaction or BF 3 ‐catalyzed intermolecular annulation (Scheme ).…”
Section: Introductionmentioning
confidence: 99%